Catalytic oxidation of aromatic VOCs with Cr or Pd-impregnated Al-pillared bentonite: Byproduct formation and deactivation studies - Alves De Oliveira, Luiz Carlos (2008)
The catalytic behavior of chromium and palladium-impregnated Al-pillared bentonite for the oxidation of aromatic VOCs, i.e. chlorobenzene or xylene, was investigated. The Cr-impregnated bentonite showed high activity for the total oxidation of cholorobenzene and xylene but the materials were completely deactivated during the reaction at 600 °C. Atomic absorption, XPS, XRD and TG analyses suggested three main causes for the deactivation, i.e. the loss of Cr due to the formation of volatile CrO2Cl2, a strong decrease on the surface area due to the collapse of the pillars and the formation of coke. For the Pd supported pillared bentonite, the impregnation procedure completely destroyed the Al-pillars but produced a very active and stable catalyst to oxidize aromatic contaminants. However, in the case of chlorobenzene almost 20% yield of the hazardous hexachlorobenzene was obtained likely by an oxychlorination process.